Combining Uranium, Boron, and Strontium Isotope Ratios (234U/238U, δ11B, 87Sr/86Sr) to Trace and Quantify Salinity Contributions to Rio Grande River in Southwestern United States - Garcia, Sandra; Louvat, Pascale; Gaillardet, Jerome; Nyachoti, Syprose; Ma, Lin (Frontiers in Water, 2021)
In semi-arid to arid regions, both anthropogenic sources (urban and agriculture) and deeper Critical Zone (groundwater with long flow paths and water residence times) may play an important role in controlling chemical exports to rivers. Here, we combined two anthropogenic isotope tracers: uranium isotope ratios (234U/238U) and boron isotope ratios (11B), with the 87Sr/86Sr ratios to identify and quantify multiple solute (salinity) sources in the Rio Grande river in southern New Mexico and western Texas. The Rio Grande river is a major source of freshwater for irrigation and municipal uses in southwestern United States. There has been a large disagreement about the dominant salinity sources to the Rio Grande and particularly significant sources are of anthropogenic (agriculture practices and shallow groundwater flows, groundwater pumping, and urban developments) and/or geological (natural groundwater upwelling) origins.